2020
DOI: 10.2147/cmar.s235777
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cancer Patient-Reported Preferences and Knowledge for Liquid Biopsies and Blood Biomarkers at a Comprehensive Cancer Center</p>

Abstract: Background: Blood-based biomarkers (liquid biopsy) are increasingly used in precision oncology. Yet, little is known about cancer patients' perspectives in clinical practice. We explored patients' depth of preferences for liquid vs tissue biopsies and knowledge regarding the role of blood biomarkers on their cancer. Methods: Three interviewer-administered trade-off scenarios and a 54-item selfadministered questionnaire were completed by cancer outpatients across all disease sites at the Princess Margaret Cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…While the vast majority of patients (85%) felt that they understood their treatment as explained to them, only 23% of physicians felt that their patients were fully informed [82]. Likewise, in a separate survey of patients at a cancer network in Canada, patients' understanding regarding their own cancer's blood-based biomarkers was low (23%), yet the majority of patients considered the development of such biomarkers as important [83]. Finally, in order to achieve successful transformative decision-making guided by tumor molecular profiling, it is imperative to build the trust between patients and their physicians; physicians are at the interface between research and real-world medicine, and physician trustworthiness is instrumental in influencing and promoting such programs [84].…”
Section: Future Perspective: Patient Organization Commentarymentioning
confidence: 99%
“…While the vast majority of patients (85%) felt that they understood their treatment as explained to them, only 23% of physicians felt that their patients were fully informed [82]. Likewise, in a separate survey of patients at a cancer network in Canada, patients' understanding regarding their own cancer's blood-based biomarkers was low (23%), yet the majority of patients considered the development of such biomarkers as important [83]. Finally, in order to achieve successful transformative decision-making guided by tumor molecular profiling, it is imperative to build the trust between patients and their physicians; physicians are at the interface between research and real-world medicine, and physician trustworthiness is instrumental in influencing and promoting such programs [84].…”
Section: Future Perspective: Patient Organization Commentarymentioning
confidence: 99%
“…Patients with cancer have reported they are more likely to prefer liquid biopsies than tissue biopsies, if the technology can provide similar information to guide treatment decisions. 75 In cases in which tissue biopsy is not feasible, liquid biopsy-based CGPs could provide an alternative to people for whom there were no previous options. 9 A study that surveyed people who underwent genomic profiling reported that most overwhelmingly favoured testing if it provides an opportunity to receive tailored treatment and avoid adverse effects of non-targeted therapies that could be less effective.…”
Section: Interpreting Complex Resultsmentioning
confidence: 99%
“…8 For LB, we assumed patients would agree to receive a blood test for cancer screening and adherence was set to 100%; this assumption was varied broadly in sensitivity analysis. 16 In the C-LB group, 60.6% of patients received colonoscopy, and all unscreened patients underwent LB. Patients at average risk received colonoscopy every 10 years, S-DNA and LB every 3 years, and FIT annually.…”
Section: Strategiesmentioning
confidence: 99%
“…[11][12][13][14] These tests have better performance than previous blood-based cancer detection tests, 15 and LBs may present a more appealing CRC screening option especially among individuals who are unscreened. 16 While there has been increasing investment in LB for its potential to detect early cancer, it remains unclear whether it is a costeffective CRC screening strategy in the US.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation